2017
DOI: 10.4149/bll_2016_128
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electromagnetic radiation (2450 MHz wireless devices) on the heart and blood tissue: role of melatonin

Abstract: OBJECTIVE: This study was designed to investigate the effects of 2450 MHz EMR on the heart and blood in rat and possible ameliorating effects of melatonin. MATERIAL AND METHOD: Thirty-two female Wistar Albino rats were randomly grouped (by eight in each group) as follows: Group I: cage-control group (dimethysulfoxide (DMSO), 10mg/kg/day i.p. without stress and EMR. Group II: sham-control rats stayed in restrainer without EMR and DMSO (10mg/kg/day i.p.). Group III: rats exposed to 2450 MHz EMR. Group IV: treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In the heart of Wistar rats, 2.45 GHz RF-EMF exposure for 5 min (50, 100, 150, 200 mW/cm 2 ) or 30 days (SAR: 0.1 W/kg) resulted in changes in ROS and oxidative stress markers and increased tissue toxicity and apoptosis [186] or in more lipid peroxidation and reduced SOD, respectively [187]. Two studies in Sprague-Dawley rats examined oxidative stress in the heart applying laboratory-generated 900 MHz RF-EMF signals.…”
Section: Oxidative Influences On Other Organsmentioning
confidence: 99%
“…In the heart of Wistar rats, 2.45 GHz RF-EMF exposure for 5 min (50, 100, 150, 200 mW/cm 2 ) or 30 days (SAR: 0.1 W/kg) resulted in changes in ROS and oxidative stress markers and increased tissue toxicity and apoptosis [186] or in more lipid peroxidation and reduced SOD, respectively [187]. Two studies in Sprague-Dawley rats examined oxidative stress in the heart applying laboratory-generated 900 MHz RF-EMF signals.…”
Section: Oxidative Influences On Other Organsmentioning
confidence: 99%
“…For these reasons, it is very important to have enough antioxidant capacity during pregnancy. Healthy nutrition and avoiding all factors that cause oxidative stress will provide a more positive pregnancy process [21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…In any case, this deserves special attention and a detailed comparative study. Although direct effect of RF-EMF exposure on melatonin has not been confirmed, several studies in the literature reported a potential protective effect of melatonin against the adverse effects induced by RF-EMF exposure, such as oxidative stress [Kerman et al, 2005;Ozguner et al, 2005a;Köylü et al, 2006;Ozguner et al, 2006;Sokolovic et al, 2008;Kesari et al, 2012;Naziroğlu et al, 2012;Aynali et al, 2013;Sokolovic et al, 2013;Meena et al, 2014;Oksay et al, 2014;Tök et al, 2014;Djordjevic et al, 2015;Sokolovic et al, 2015;Gumral et al, 2016;Pandey and Giri 2018], DNA damage [Lai and Singh, 1997;Liu et al, 2013;Sokolovic et al, 2015;Pandey and Giri, 2018], neuroprotective effects [Erdem Koc et al, 2016], histopathologic changes in skin [Ayata et al, 2004;Ozguner et al, 2004), and adverse effects of EMF on the kidneys [Oktem et al, 2005;Ozguner et al, 2005b;Ulubay et al, 2015] or liver [Gökcimen et al, 2002]. Even though melatonin secretion is not affected by RF-EMF exposure, it seems to play an important role in the protection of the organism from oxidative stress induced by RF-EMF exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of reports then looked at the non‐thermal effects of exposure to RF on cancer while others dealt with physiological functions [van Rongen et al, 2009; Ghosn et al, 2012, 2015], endocrine system, fertility, genotoxicity [Saliev et al, 2019; Vijayalaxmi and Prihoda, 2019], sleep [Danker‐Hopfe et al, 2016; Lowden et al, 2019], etc. Many models have been used, ranging from cell cultures and in vivo effects of exposure on laboratory animals to clinical and epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%